Influência do transtorno depressivo maior e dos transtornos de ansiedade na qualidade de vida de pacientes com hepatite C crônica - Luciana Rodrigues da Cunha (2012)
Several studies including chronic hepatitis C (CHC) patients reportreduced health-related quality of life (HRQOL) as compared with healthy controls, regardless of the liver disease stage. Mood, illness severity and health behaviour affect HRQOL in various chronic disorders. In the case of HCV infection, the interrelationships amongst these biopsychosocial factors are not fully understood. Aims: The main purpose of the present study was (1) to evaluate HRQOL in CHC patients referred to the Viral Hepatitis Ambulatory (AHEV-IAG-HC-UFMG). Additionally, we aimed to (2) evaluate factors (sociodemographics, clinical characteristics, psychiatric comorbidities and viral characteristics) that may influence HRQOL and (3) assess the impact of major depression disorder (MDD) and anxietydisorders on HRQOL of the participants in this study. Patients and Methods: Patients with CHC diagnosis (n=125 HCV RNA-positive) who provided written consent were prospectively enrolled. All patients completed several surveys including Mini-International Neuropsychiatry Interview (MINI-Plus 5.0), Hamilton Depression Rating Scale (HDRS), Hospital Anxiety and Depression Scale (HADS). HRQOL wasevaluated by Liver Disease Quality of Life Questionnaire (LDQOL1.0), consisting of the SF-36 generic measure of HRQOL and 12 disease-specific dimensions for patients with liver disease. The protocol was approved by the Ethical Committee of UFMG. Data were analyzed by SPSS 17.0. Multiple linear regression analyses were used in order to quantify the simultaneous and mutually independent contribution ofclinical, psychiatric and sociodemographic variables. Independent variables were grouped as sociodemographic (age, gender, marital status, family income and education), health behaviour (tabagism), clinical characteristics [liver cirrhosis, body mass index (BMI), hypertension and diabetes], psychiatric comorbidities (currentMDD, anxiety disorders, current and/or past alcohol abuse or dependency, current and/or past illicit drugs abuse or dependency), viral characteristics (viral load and genotype) and biochemical data [alanine aminotransferase (ALT)]. Variables with p<0.20 in the univariate analysis were selected for the multivariate analysis. In each group of variables, when more than one had p<0.20, hierarchical linear regressionmodels were created for the selection of those actually associated with the reduction of LDQOL dimensions scores. At the final multivariate regression model only the variables of each group with p<0.05 were included. The adjusted R² (determination coefficient) and ANOVA test were used to evaluate models adequacy. Results: Baseline characteristics of CHC patients were: mean age 53.2 ± 11.6 yrs; 57.6%,female; 16.8%, compensated cirrhosis, 28.8%, current MDD and 23.2%, anxiety disorders. MDD was associated with lower LDQOL scores in 10 domains, excluding sexual function (p=0.15) and sexual problems (p=0.43), independently of liver stage disease. Anxiety disorders were associated with lower LDQOL scores in three domains: health distress (p=0.003), stigma of liver disease (p=0.007) and sexual problems (p=0.004). Worse quality of life was found in patients with current or past alcohol abuse or dependency for the domain loneliness (p=0.009). Cirrhosis and diabetes were associated with lower LDQOL scores in two domains: sexual function (p=0.02) and sexual problems (p=0.05), respectively. Higher levels of educationwere associated with lower LDQOL scores in three dimensions: health distress (p=0.02), hopelessness (p=0.02) and stigma of liver disease (p=0.04). In addition, the negative correlation between the severity of MDD and anxiety disorders and HRQOL was observed. Conclusions: Various factors, other than the hepatopathy itself, affect HRQOL of CHC patients. Thus, a broad clinical assessment becomesrelevant in medical attendance of these individuals, and mental health aspects in particular should be investigated criteriously. The adoption of a biopsychosocial model with the purpose of improving HRQOL among patients living with hepatitis C should be a goal to be accomplished by the interdisciplinary and multiprofessional AHEV-IAG-HC-UFMG team.